Construction and immunological evaluation of recombinant adenovirus vaccines of new novel NADC34-PRRSV strains in pigs - Xie, Chang-zhan; Zhang, Ping; Wang, Zheng; Tao, Yi-mo; Cui, Zhuo-dong; Nan, Fu-long; Zhang, Fu-chao; Ren, Yun-xin; Zhang, He; Lu, Hui-jun (Frontiers in Veterinary Science, 2024)
IntroductionPorcine reproductive and respiratory syndrome virus (PRRSV) causes reproductive and respiratory diseases in sow herds and piglets. The emergence of ORF5 RFLP 1–7-4-like (NADC34-like) PRRSV strain in China has brought a new round of challenges to PRRSV prevention.MethodsIn addition, recombinant adenovirus vaccine candidates against the newly emerged NADC34-like strain were constructed in the study; the immunogenicity of the vaccine was investigated in piglets. After inoculation with PRRSV recombinant adenovirus, specific antibodies, neutralizing antibodies, and levels of IFN-γ and IL-4 cytokines were detected in serum.ResultsThirty-five days after immunization, the levels of IFN-γ and IL-4 cytokines in the pac-Ad5-34-GP3, pac-Ad5-34-GP5, and pac-Ad5-34-GP35 experimental groups were significantly higher (p < 0.05) than those of the PBS and the adenovirus group. All vaccines can cause corresponding Th1 and Th2 immune responses based on animal experimental results. After the challenge, no obvious clinical symptoms were observed in the immune groups compared with the control group, vaccinated animals could reduce the occurrence of viremia, and the occurrence of viremia was alleviated, with no obvious pathological changes in the lungs, indicating that recombinant adenovirus vaccine could provide a good protective immunity and produce a good humoral and cellular immune response at the same time.DiscussionIt shows that the recombinant adenovirus vaccine group has better protection against the virus. Provide vaccine reserve and theoretical support for the emergence of new PRRSV subtypes in China.